Pengaruh Penerapan Ongoing Assesment dalam Pembelajaran CTL Menggunakan Flip Chart - Della Dwi Andhini; Undang Rosidin; Kartini Herlina (Jurnal Penelitian Pendidikan IPA, 2020)
This study aims to determine the effect of ongoing assesment in collaborative teamwork learning using flip chart on students’ collaborative abilities and cognitive skills. This research design used was one shot case design and one group pretest-posttest design. This study used one experiment class and students were given special treatment or teaching for some time. This treatment is the use of ongoing assessment in collaborative teamwork learning using flip chart on students’. The research data was taken from the value of observations and initial and final tests whose results were tested using the simple linear regression. Based on the results of the first hypothesis and the second hypothesis testing using simple linear regression with Asymp.Sig. (2-tailed) are both obtained 0,00 so H0 is rejected, which means the effect of ongoing assesment in collaborative teamwork learning using flip chart format influences the increase of collaborative abilities and cognitive skills. based on the value of the correlation coefficient (r) in the simple linear regression test obtained 0.42 for the first hypothesis test which means, the effect of ongoing assessment incollaborative teamwork learning using flip charts has a good enough effect on collaborative abilities, which is equal to 42%. Whereas in the second hypothesis test the correlation coefficient value (r) obtained in a simple linear regression test obtained 0.90, which means, the effect of ongoing assessment in collaborative teamwork learning using flip charts has a very good effect on cognitive skills, which is equal to 90%.